Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To determine if [tex]\( y = 53 \)[/tex] is a solution of the equation [tex]\( 6y + 10 = 12y \)[/tex], we will substitute [tex]\( y = 53 \)[/tex] into the equation and verify if both sides are equal.
1. Substitute [tex]\( y = 53 \)[/tex] into the left side of the equation [tex]\( 6y + 10 \)[/tex]:
[tex]\[ 6 \cdot 53 + 10 \][/tex]
First, calculate [tex]\( 6 \cdot 53 \)[/tex]:
[tex]\[ 6 \cdot 53 = 318 \][/tex]
Next, add 10:
[tex]\[ 318 + 10 = 328 \][/tex]
So, the left side of the equation, when [tex]\( y = 53 \)[/tex], is 328.
2. Substitute [tex]\( y = 53 \)[/tex] into the right side of the equation [tex]\( 12y \)[/tex]:
[tex]\[ 12 \cdot 53 \][/tex]
Calculate [tex]\( 12 \cdot 53 \)[/tex]:
[tex]\[ 12 \cdot 53 = 636 \][/tex]
So, the right side of the equation, when [tex]\( y = 53 \)[/tex], is 636.
3. Compare both sides of the equation:
[tex]\[ 328 \text{ (left side)} \neq 636 \text{ (right side)} \][/tex]
Since 328 is not equal to 636, the equation [tex]\( 6y + 10 = 12y \)[/tex] does not hold true when [tex]\( y = 53 \)[/tex].
Therefore, [tex]\( y = 53 \)[/tex] is not a solution to the equation [tex]\( 6y + 10 = 12y \)[/tex].
1. Substitute [tex]\( y = 53 \)[/tex] into the left side of the equation [tex]\( 6y + 10 \)[/tex]:
[tex]\[ 6 \cdot 53 + 10 \][/tex]
First, calculate [tex]\( 6 \cdot 53 \)[/tex]:
[tex]\[ 6 \cdot 53 = 318 \][/tex]
Next, add 10:
[tex]\[ 318 + 10 = 328 \][/tex]
So, the left side of the equation, when [tex]\( y = 53 \)[/tex], is 328.
2. Substitute [tex]\( y = 53 \)[/tex] into the right side of the equation [tex]\( 12y \)[/tex]:
[tex]\[ 12 \cdot 53 \][/tex]
Calculate [tex]\( 12 \cdot 53 \)[/tex]:
[tex]\[ 12 \cdot 53 = 636 \][/tex]
So, the right side of the equation, when [tex]\( y = 53 \)[/tex], is 636.
3. Compare both sides of the equation:
[tex]\[ 328 \text{ (left side)} \neq 636 \text{ (right side)} \][/tex]
Since 328 is not equal to 636, the equation [tex]\( 6y + 10 = 12y \)[/tex] does not hold true when [tex]\( y = 53 \)[/tex].
Therefore, [tex]\( y = 53 \)[/tex] is not a solution to the equation [tex]\( 6y + 10 = 12y \)[/tex].
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.